Wild Stinging Nettle (Urtica dioica) Extract Suppresses Visceral Adipose Aromatase Levels and Improves Lipid Profile in Male Obese Rats - Zaenudin, Zaenudin; Tyas, Jurnalis Gempaning; Tangkari, Kabir Ardiansyah; Sutiani, Harni; Farmawati, Arta; Prasetyastuti, Prasetyastuti (Journal of Food and Culinary, 2025)
Obesity can elevate estrogen levels through increased aromatase activity, adversely affecting male fertility. Although aromatase inhibitors are commonly used, they can disrupt lipid profiles and raise cardiovascular risks. This experimental study analyzed the effects of wild stinging nettle (Urtica dioica) extract on visceral adipose aromatase levels and serum lipid profiles in obese male rats. Twenty-five 7–8-week-old male Sprague Dawley rats were divided into five groups: normal control, obesity control, and three obesity groups receiving U. dioica extract at 125, 250, or 500 mg/kg body weight. After a 4-week intervention, blood samples were collected to measure lipid profiles, and visceral adipose tissue was harvested to assess aromatase levels. The U. dioica extract significantly reduced visceral adipose aromatase levels (p < 0.01) and improved lipid profiles in obese rats. Specifically, treated rats showed dose-dependent decreases in triglycerides, total cholesterol, and LDL-cholesterol, along with an increase in HDL-cholesterol (p < 0.05). These findings indicate that U. dioica extract can suppress adipose aromatase levels and ameliorate lipid disturbances in obesity.